Magnetorheological Finishing of Polymers for Improving the Surface Finish - Arora, Kunal (My University, 2022)
In the present scenario, different shaped polymer components with improved functional performance are desired in the automobile, medical, and aerospace industries. Polymer gears, bearings, and bushings have replaced metal counterparts in various equipment such as micro, and macro devices, automotive equipment, farm and agricultural equipment, electrical toys, and marine transmission. Similarly, polymers play important role in the medical industry as they are notably used in hip joint implants, knee joint implants, dental X-ray systems, surgical robotic drives, etc. This is because the polymer-based components offer unique advantages over the metal components such as low weight, good corrosion-resistant, extremely good formability, compatibility, and ability to function without external lubrication with minimum noise and vibration. The uniform fine finishing of these polymer components is an important need of the various industrial machines for enhancing their efficacy. For the finishing of the polymer components, various traditional and advanced finishing processes are developed such as grinding, ball burnishing, chemo-mechanical process, etc. However, finishing the polymer workpieces with these processes can produce uncontrolled finishing forces. Owing to this, several surface defects such as micro-cracks, scars, etc. appear on the finished surface of the polymer workpieces. To achieve efficient and defect-free finished surfaces of polymers, magnetorheological polishing (MRP) fluid-based finishing processes are utilized. The magnetorheological finishing (MRF) process provides a fine grade of surface finish with a minimal scar. The MRF process uses MRP fluid which includes the electrolytic iron particles, polishing grade abrasives, and the carrier fluid. The MR fluid-based finishing process does not leave pits or scratches. The process also has the potential to achieve nanoscale precision without causing harm to the workpiece's surface or sub-surface. Since the MR finishing has provided fine finishing over various optical applications and offers a clean and damage-free surface due to low normal forces on abrasives. Therefore, the MR finishing process can also be used for the polymer components which are used in various industries such as automobile, medical, marine, etc. Hence, in the present work, the advantage of the magnetorheological finishing process has been explored further for the fine finishing of various polymer industrial components with different shapes such as gears, bearings, valve seats, medical implants, and additive manufactured components, etc. Therefore, different magnetically controllable finishing tools, as well as workpiece fixtures, are designed and fabricated to fine finish these polymer workpieces. For the design of the different magnetorheological finishing (MRF) tools, magnetostatic finite element analysis (MFEA) is performed. The MFEA is used to determine the required value of magnetic flux density (MFD) on the MR finishing tool's surface. The different MR finishing tools are designed as per the shape of the workpiece (flat, internal, hemispherical, gears). In all the cases, the MFEA result reveals the ability to retain the magnetorheological polishing (MRP) fluid over the tool surface for fine finishing the various shapes of polymer workpieces. The decreasing MFD value amid the working gap ensures that iron particles are retained on the tool surface and abrasive particles present in the MR polishing fluid perform proper relative motion over the polymer workpiece surface. Hence, the present developed finishing tools are feasible to provide fine finishing over the different types and shapes of polymer workpiece surfaces. Further, the magnetic flux density is also analyzed experimentally over the different fabricated MR finishing tools. It is found that the MR finishing tools provide uniform magnetic flux density over the tool surface which may lead to the fine finishing of the polymer workpieces. Further, the workpiece fixture and holders are designed and fabricated as per the shape of the workpiece to be finished. The fixtures are designed in such a way that a uniform working gap could be maintained between the tool surface and workpiece surface during the finishing process. Also, the fixtures are designed so that workpiece remains tight against different motions while finishing. After the fabrication of tools and fixtures, to get insight into the process mechanism, the material removal by the different fabricated MR finishing tools over the polymer workpieces is analyzed. Because different shapes of polymer workpieces (flat, internal, hemispherical, gears, etc.) are finished in the current work, various types of motions are used for finishing, resulting in various forces acting. Further, theoretical analysis is performed to understand the process mechanism during the finishing of the flat, hemispherical, and gear surface using the newly developed magnetorheological finishing tools. The influence of the magnetic flux density, the path followed and the number of active abrasive particles have been explored in depth using theoretical analysis. Also, in the theoretical analysis, a surface roughness model is developed to predict the finishing of the different surfaces with the present magnetorheological finishing tools. From the theoretical model for the hemispherical cup, the percentage error amid the experimentally obtained values and the theoretically calculated value is in the range of 1.17 to 6.15 %. Similarly, for gear and flat surface, the percentage error amid the experimentally obtained values and the theoretically calculated value is in the range of 2.3 to 10 % and 0.55 to 9.09 %, respectively. Thus, from the results of the theoretical analysis, it is found that the MR finishing tools are capable for fine finishing the different shapes of polymer workpieces. In the magnetorheological finishing (MRF) process, the MR polishing (MRP) fluid plays an important role, therefore, the effectiveness of the MRP fluid over the different polymer materials has been further analyzed. For this, the different MRP fluids are developed and experimentally tested over the polymer materials. The results reveal that water-based MRP fluid shows significantly effective finishing over polyamide surfaces as compared to the oil-based MRP fluid. Also, MRP fluid with CeO2 abrasives is found more effective for fine finishing the UHMWPE polymer as compared to the SiC and Al2O3 abrasives. Additionally, the graphene-based MRP fluid is found effective for fine finishing of the polymers as compared to the non-graphene-based MRP fluid. Further, to validate the efficacy of MR finishing tools for finishing the polyamide workpiece surface, preliminary experimentation is performed over the external flat cylindrical surface of the polyamide component. The process parameters magnetizing current, rotational tool speed, reciprocation tool speed, and rotational speed of workpiece are used for investigating the fine finish of the polyamide workpieces. The response surface method is further used to find the best process parameters for the fine finishing of the polyamide workpiece surfaces. In the 100 min of the finishing cycle, the surface roughness on a polyamide surface area of 706.5 mm2 is reduced to 100 nm from 560 nm. Furthermore, after the validation of the fine finishing of the polyamide workpiece surface, a detailed experimental study has been done for various polymer components such as acetabular cups, gears, bearings, valve seals and additive manufactured components. UHMWPE is used for the manufacturing of acetabular cups in hip-joint implantation. For enhancing the life span and functionality of hip implants, the uniform fine surface finish of the acetabular cup is essential. For the fine finishing of the cups, the hemispherical tip-based magnetorheological finishing tool is used. After the experimentation on the 1140 mm2 surface area of the UHMWPE acetabular cup, the surface improvement obtained is 66.67 % in 100 min of the finishing cycle. Scanning electron microscopy, a coordinate measuring machine, and a microhardness tester machine are used to examine the surface morphology, circularity, and microhardness of the finished UHMWPE acetabular cup. Results show that the present process is suitable for the uniform fine finishing of the UHMWPE acetabular cup with improved surface characteristics. Fine finishing of polymer bevel gears (BGs) plays a key role in defining the functionality of many industrial components. Polymer BGs are highly utilized due to their properties such as high damping resistance and low weight. A novel magnetorheological bevel gear finishing (MRBGF) process is utilized to finish the overall polyamide BG surface in minimum time. After experimentations, the average surface roughness value of the overall polymer BG got reduced from 380 nm to 100 nm in 140 min finishing with predicted optimum parameters. Microhardness and surface morphology are also used to assess MRBGF process efficacy and BG tooth accuracy. The results reveal significant improvement in surface characteristics and an increase in average microhardness of the BG tooth surface. Also, gear run-out is reduced from DIN 8 to DIN 6 which demonstrates improvement in BG tooth accuracy. Fine finishing of the internal polymer bearing is an important factor in deciding the surface quality of the manufactured products. Finely finished polymer bearing internal surface is highly utilized in several industries such as food, textile, etc. Fine finishing of the polytetrafluoroethylene (PTFE) internal surface has been done using the newly developed rotational magnetorheological (R-MR) honing process. After experimentation on the 4772.80 mm2 surface area of bearing, the percentage of surface improvement obtained is 82.5% in 120 min of finishing. A study of surface morphology and dimensional accuracy over the PTFE bearing surface is also carried out to evaluate the efficacy of the current R-MR honing process. Results show that the current approach is capable of uniform fine finishing of the internal surface of PTFE bearings with enhancement in surface characteristics and functional efficacy. The polymer valve seat is an important part of the ball valves in the pipeline which are used for transporting the medium such as oil and gas from one place to another. However, during the practical application, inevitable events of the leakage of the pipeline valves during the gas or oil transportation process pose serious problems. Hence, the fine finishing of the polymer valve seat is of significant importance. For fine finishing of the polymer valve seat surface using magnetorheological (MR) finishing process with the hemispherical tip-based electromagnetic tool is used. After experimentation on the 4878 mm2 surface area of the polymer valve seat, the % ∆Ra obtained is 80.70 % in 140 min of finishing using the optimum process parameters. The dimensional accuracy of the valve seat surface is further analyzed in terms of circularity. Results show that the current method is capable of uniform fine finishing of the polymer valve seat surface with enhancement in surface characteristics. Fused deposition modeling (FDM) is a common and cost-effective additive manufacturing technique for making cylindrical components such as printer rollers, turbine blades, and winding drums. The fine finishing tends to enhance dimensional accuracy and efficacy of FDM fabricated cylindrical components. The best process parameters are further utilized for the surface improvement of FDM workpieces. After experimentation on 18,840 mm2 cylindrical surface area, % ΔRa obtained is 86.44 % in 140 min of finishing. To analyze present MRF process efficacy, a study of circularity, surface morphology, microhardness, waviness, and wear test is done. After finishing, the dimensional accuracy and surface characteristics show a substantial improvement. All of these findings suggest that a novel hexagonal tool tip-based MRF process may be used to fine-finish the FDM-fabricated workpieces. All these results signify that the presently developed magnetorheological finishing tools can be found to be effective for fine finishing of the various polymer workpieces with different shapes which can be beneficial for various industrial components such as gears, bearings, acetabular cups, and additive manufacturing components.
Keywords: Different shapes of polymers’ surface; magnetorheological (MR) finishing; various shapes of magnetic tools’ surface; magnetic field; MR polishing fluids; additive manufacturing components; surface roughness; surface characteristics